Duration of strong ground motion during Mexican earthquakes in terms of magnitude, distance of the rupture area and dominant site period. - Reinoso, Eduardo (Earthquake engineering & structural dynamics.)
A study of the duration of strong ground motion using accelerometric data of subduction and normal faulting Mexican earthquakes is presented. Duration is obtained based on the time between 2.5 and 97.5 per cent of the Arias intensity. An expression to predict this duration in terms of the magnitude , distance to the rupture area and site period is proposed and compared with predictions available in the literature. The effect of large duration for very distant sites and the contribution of soft soils to the duration of strong ground motion are widely discussed. We have found that large magnitude not only yields long duration at the source, but also proportionally longer duration with distance and with dominant site period compared to small magnitude. The duration obtained from the regression is used as a parameter to obtain input and hysteretic energy and on the use of damage models available in the literature. Finally, duration is used together with the random vibration theory to predict response spectra.